Classical presentation of Gardner's syndrome in an Indian patient: A case report - Priyanka Verma; Varun Surya; Sonali Kadam; Hemant R Umarji (Wolters Kluwer Medknow Publications, 2016)
Gardner's syndrome is an autosomal dominant disease characterized by the presence of colonic polyposis, osteomas, and a multitude of soft-tissue tumors. Dental anomalies are present in estimated 30% of all affected individuals of Gardner's syndrome, so dental professionals play an important role in determining the early signs of the syndrome. The intestinal polyps have a 100% risk of undergoing malignant transformation if not treated thus, early diagnosis and regular surveillance are important. In this report, we describe classical presentation of Gardner's syndrome in a patient who presented with bilateral swellings on palate along with multiple impacted teeth.